'A GREAT KICK AT MISERY': D. H. LAWRENCE'S SENSE OF TRAGEDY†. (28th August 2015) - Dean, Paul
Abstract: This essay considers whether Lawrence can properly be called a tragic novelist and whether there can be such a thing as a tragic novel. Discussion concentrates on The Trespasser and Women in Love, but reference is also made to other fiction and essays by Lawrence. His developing views about the novel, catalysed in his early work by his study of Thomas Hardy, led him gradually away from a philosophy of romantic pessimism towards an affirmation of the human potential for fullness and growth. Individuals who refuse to be open to these possibilities may be described as tragic, but the thrust of Lawrence's mature fiction is to present them with understanding and compassion while refraining from generalizing from their experiences to the human condition as a whole.